Nutritional status, food consumption and nutritional monitoring practice of children and adolescents with autism spectrum disorder - da Costa, Francieli Rodrigues; Scherer, Alana Luisa; Vogel, Patricia; Conde, Simara Rufatto; Adami, Fernanda Scherer; Fassina, Patricia (Seven Editora, 2023)
Objective: To evaluate the nutritional status, food consumption, and nutritional monitoring of children and adolescents with autism spectrum disorder (ASD). Methods: Cross-sectional, quantitative study, carried out between September and October 2022, with 8 individuals aged 5 to 14 years, diagnosed with ASD, enrolled in 5 municipal schools in a municipality in Rio Grande do Sul. Data on name, sex, date of birth, the practice of nutritional monitoring, weight, and height were collected to assess the nutritional status through the Body Mass Index for age, according to the growth curves of the World Health Organization (WHO, 2007), in addition to 2 24-hour food recalls, considering the average consumption of both referring to the total energy value (TEV),  macronutrients (carbohydrates, proteins, and lipids) and micronutrients (iron, zinc, magnesium, vitamin A, C, and D ), which were compared with the Dietary Reference Intakes (DRIs). Results: Regarding nutritional status, 50% (n=4) were eutrophic, 12.5% (n=1) overweight and 37.5% (n=3) obese, with 100% (n= 8) did not perform nutritional follow-up. Intake of TEV and macronutrients was by the daily recommendation, while micronutrients were inadequate. Fresh foods were the basis of the evaluated diet. Conclusion: A considerable portion was overweight. The dietary intake of TEV and macronutrients was in line with daily recommendations, while micronutrients were inadequate. None of the individuals with ASD practiced nutritional monitoring with a professional nutritionist.DOI:https://doi.org/10.56238/alookdevelopv1-140